2004
DOI: 10.1016/j.molcel.2004.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Yeast Telomerase to a DNA Break Depends on the Recruitment Functions of Cdc13 and Est1

Abstract: The yeast single-strand TG-repeat telomere binding protein Cdc13 and the telomerase accessory protein Est1 play essential roles in chromosome end replication. To determine whether a proposed Cdc13-Est1 interaction recruits telomerase (Est2), we used a simplified system in which telomere formation was monitored at an HO-induced DNA double-strand break (DSB). Tethering of either Cdc13 or Est1 adjacent to a DSB promoted telomere formation, and tethering of Est1, even in the absence of a DSB, resulted in the recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
161
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(177 citation statements)
references
References 39 publications
15
161
1
Order By: Relevance
“…4C). Our data agree with prior in vivo studies showing that Est1 and Est2 interact in a tlc1-null background and that human Est1A associates directly with the reverse transcriptase subunit in vitro (5,11). However, the interaction is less efficient in the absence of Tlc1, which suggests that the Tlc1 RNA fosters assembly of the complex, as has been previously suggested (12,13).…”
Section: Est1supporting
confidence: 92%
See 1 more Smart Citation
“…4C). Our data agree with prior in vivo studies showing that Est1 and Est2 interact in a tlc1-null background and that human Est1A associates directly with the reverse transcriptase subunit in vitro (5,11). However, the interaction is less efficient in the absence of Tlc1, which suggests that the Tlc1 RNA fosters assembly of the complex, as has been previously suggested (12,13).…”
Section: Est1supporting
confidence: 92%
“…Supporting a requisite Est1-Cdc13 interaction for proper telomerase regulation are reciprocal-charge mutants [e.g., est1-60 (K444E) suppresses cdc13-2 (E252K)] that separately lead to telomere DNA shortening (4). Since Est1-60 can bind telomerase in vivo, it was proposed that the K444E mutation disrupts Cdc13 association (4,5). However, other studies suggest that the Cdc13-2 mutation does not disrupt Est1 interactions since wild-type Est1 interacts with Cdc13 and Cdc13-2 in vivo (6)(7)(8).…”
mentioning
confidence: 99%
“…Both an aliquot of sonicated cleared extract (input) and the immunoprecipitated material were de-cross-linked in TE (Tris-EDTA) plus 1% SDS for at least 8 h at 65°C. Quantitation of immunoprecipitated DNA was obtained by real-time PCR using SYBR Green detection (Bianchi et al, 2004) on an Applied Biosystems ABI Prism 7700 machine (Foster City, CA). Primers used were RPL2B-5Ј (CAGAGAGGTCGTCCCAGTCT) and RPL2B-3Ј (GCA-GAATCCACCAGGAGTGT) for RPL2B promoter and HL228 (GAATT-GAGAGTTGCCCCAGA) and HL229 (AGAAGGCTGGAACGTTGAAA) for the ACT1 gene.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%
“…These data are consistent with a simple model in which Cdc13 binds to the ssDNA of a processed DSB and recruits Est1 by a direct interaction. 14 …”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, Shore and colleagues have demonstrated that Cdc13 and Ku70/ Ku80 cooperate in the recruitment of Est2 to an HO-induced DSB. 14 To test the possibility that Ku70-dependent recruitment of the telomerase machinery may also contribute to peripheral localization of a persistent DSB, we monitored recruitment of Mps3 to a persistent DSB in isogenic wildtype and ku70Δ strains (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%